Znaczenie nauczania hybrydowego w procesach zarządzania organizacji opartej na wiedzy - Głowicki, Piotr; Łasiński, Gabriel (Signification of blended learning in knowledge based organizations management processes, 2005)
Article is a attempt to show a Blended Learning as contemporary tool with is very important in contemporary organization. There is an argument placed, that the blended learning led in a systematic way, may essentially conduce to processes improving. These processes are connected with education and many other elements of contemporary organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 246-252